PENERAPAN MODEL MORAL REASONING UNTUK MENINGKATKAN KEBERANIAN MENGEMUKAKAN PENDAPAT DAN SIKAP TERHADAP KASUS HAM DI SMP NEGERI 2 BANJAR MARGO KABUPATEN TULANG BAWANG - Haris Tri Okfianto; Adelina Hasyim; Pargito Pargito (Faculty of Teacher Training and Education, University of Lampung, 2013)
The research purpose to forward any argument increase courage and attitude express towards human Rights in the Case of Citizenship Education Subject matter of human rights especially in the first semester of Grade 7 students at SMP Negeri 2 Banjar Margo Regency Tulang Bawang Academic Year 2011/2012 used the Model Moral Reasoning. This research Classroom Action Research carried out in 3 cycles of action. In this reseach, the data obtained are in the form of students 'learning and students' attitudes courage to express opinions. The instruments used are observation sheets and sheets of observations performance educator, attitude observation, field notes and documentation. The results showing that using Moral Reasoning Model to Increase Courage To put Opinions and Attitudes Toward Taking a human rights case. This indicated by the average percentage of the activity and courage to express opinions and cared students' rights cases in the cycle. The first cycle the percentage of student activity and percentage 55.18% 52.50% student achievement. In the second cycle the percentage of student activity increased to 64.51%. The third cycle, the percentage of student activity increased to 83.33%. Based on the discussion of the research that learning to model Moral Reasoning to improve Courage Opinions and Attitudes toward Taking Case subject Civic Education Human Rights on human rights in particular material on the seventh grade students in semester 1 SMP Negeri 2 Banjar Margo Regency Tulang Bawang Academic Year 2011/2012. Keywords: Moral Reasoning, moral dilemmas, Courage, human rights casesKeywords: moral reasoning, moral dilemmas, courage, human rights cases